Anticoagulation Treatment and Outcomes of Venous Thromboembolism by Weight and Body Mass Index: Insights From the Veterans Health Administration. Issue 11 (November 2021) - Perino, Alexander C.; Fan, Jun; Schmitt, Susan; Guo, Jennifer D.; Hlavacek, Patrick; Din, Natasha; Kothari, Mitra; Pundi, Krishna; Russ, Cristina; Emir, Birol; Turakhia, Mintu P.
Abstract : Background: Consensus statements have recommended against the use of direct oral anticoagulants (DOACs) in venous thromboembolism (VTE) for patients ≥120 kg and ≥40 kg/m 2 . We sought to determine use and outcomes of DOACs for VTE across weight and body mass index (BMI). Methods: We performed a retrospective cohort study of patients with first-time VTE 2013 to 2018 that were treated with DOAC or warfarin in the Veterans Health Administration. The Veterans Health Administration has implemented system-wide guidance for patient selection and shared decision-making for use of DOACs in VTE at extremes of weight. We stratified patients by weight and BMI and assessed (1) association of weight and BMI category to outcomes in those prescribed DOAC; and (2) association of DOAC, as compared to warfarin, to outcomes by weight and BMI categories. Outcomes of interest included major bleeding, clinically relevant nonmajor bleeding, and recurrent VTE. Results: The analysis cohort included 51 871 patients prescribed DOAC or warfarin within 30 days of index VTE diagnosis (age 64.5±13.1 years; 6.0% female; median weight 93.4 kg [25th–75th: 80.5–108.6 kg]). For patients ≥120 kg (N=6934 patients), 38.4% were treated with DOAC, as compared to 45.4% of those ≥60 to <100 kg (N=30 645; P <0.0001). DOAC prescription was not associated with major bleeds, clinically relevant nonmajor bleeds, or recurrent VTE for those in higher weight and BMI categories as compared to those in average weight and BMI categories. DOAC prescription, as compared to warfarin, was not associated with increased recurrent VTE in any weight or BMI category. Conclusions: Patients ≥120 kg and ≥40 kg/m 2 with VTE are frequently prescribed DOAC by the Veterans Health Administration, without an increase in bleeding or recurrent VTE. These findings suggest DOACs can be safe and effective in this population and may argue for broader adoption of pharmacy policies that promote careful patient selection and shared decision making. Abstract : Supplemental Digital Content is available in the text.